Collagen Hydrogel as Bio Interactive dressing for wound healing - Hema, G. S.; Ganesan, B.; Shyni, K.; Joshy, C. G.; Ninan, George; Mathew, Suseela (Fishery Technology, 2017)
In the present study, wound healing efficacy of thehydrogel prepared from fish skin collagen wasevaluated in experimental full thickness woundsusing albino rat model. The study demonstrated thatwithin 2 weeks, the wound covered with gel werecompletely filled with new epithelium without anysignificant adverse reactions. The results clearlysuggest that the hydrogel enhances re-epithelializationrather than a repair which was clear from thehistopathology and biochemical analysis. There issignificant increase in angiogenesis, collagen deposition,hexosamine content, epithelialization and woundcontraction in hydrogel treated rats without inflammatorycells compared to the control group, indicatingthe tissue regeneration potential of fish collagen.